O curr??culo da rede estadual de ensino de S??o Paulo an??lise e cr??tica das professoras de educa????o f??sica - Dias, Renato de S?? (2016)
In 2008, the S??o Paulo State Secretary of Education announced a new curriculum proposal for all schools in the state public school system. In 2010, this curriculum proposal became the official curriculum. This research object of study is the proposed curriculum for the subject of physical education. The central question to guide our research was to try to understand how physical education teachers that work in state schools understand, analyze and incorporate the official curriculum objectives, and procedures, and educational concepts, and guidelines into their routine and school practice. Research sources are constituted of official documents that support the proposal such as the base document, the teacher's notebook and student's notebook, the regulatory framework produced by SEE-SP and two interviews with physical education teachers. Interviews set teachers??? educational background, their understanding of the curriculum debate, their analysis of the implementation process and how the proposals present in the curriculum have been incorporated in their daily work at school. In this process, the text initially presents different curriculum theories that inform the current debate to show the approximations and distances with the official curriculum. Following, it presents the official curriculum, its foundations, guidelines and structural axes. At the end, it presents physical education teachers speeches, specifically relating their training to their understanding of curriculum processes, their reading of the official curriculum, the criticism they manifest, the experiences built daily to deal with the curriculum. In the face of the findings in this research, it is possible to state that there is little understanding of the curricular debate among teachers and that the resistance or acceptance they manifest in relation to the official curriculum is guided by a conception of education, which they understand to be critical and disruptive of the official discourse. The practices that they report show critics to the curriculum objectives, specifically to its imposition and linking with the pedagogy of competencies.